Anti-Inflammatory and Antinociceptive Properties of three Local Channa Species Crude Extracts - Mohd Hasan, Solihah (2005)
Water extract and aqueous portion of chloroform:methanol extract of Channu striatus (haruan), Channa micropeltes (toman) and Channa luciw (bujuk) wcre tested for its anti-inflammatory and antinociceptive properties. The anti-inflammatory activity of the extracts was investigated by three chemical mediators induced rat paw edema (acute inflammation) and cotton pellet granuloma in rats (chronic inflammatory modulation testing). The antinociceptive or analgesic properties were investigated by abdominal constriction test and hot plate test. The results showed that the percentage edema inhibition increased with increased in time interval and was found to be maximal at 4 hours after prostaglandin D2 injection. The effects of 60 mgkg body weight aqueous portion of chloroform:methanol extract of Channa lucius and Channa micropeltes, piroxicam (10 mg/kg) and water extract of Channa striatus (60 mg/kg) exhibited 85.4%, 79.8%, 84.3% and 78.7% edema inhibition at 4 hours respectively. However, all three local Channa spp. extracts did not show significant inhibition (p>0.05) on histamine and bradykinin induced paw edema. In the cotton pellet induced granuloma, the percentage inhibition of anti- transudative was significantly different (p<0.05) by the water extract of Channa striatus (38.1%) and Channa micropelfes (30.3%) compared to the water extract of Channa lucius (10.8%) in inhibiting wet weight of the cotton pelletinduced granuloma formation in rats. Piroxicam showed significant inhibition (p<0.05) by 30.92% and mefenamic acid (13.28%) in inhibiting wet weight granuloma. The water extract of Channa striatus and Channa micropelfes exhibited anti-transudative activity but Channa lucius was devoid of this property. Both extracts of three local Channa spp. did not show anti-proliferative activity. The aqueous portion of chloroform:methanol extract of Channa striatus (60 mglkg) and mefenamic acid (10 mg/kg) increased the serum albumin levels at 24.83 * 4.09 g/dL and 24.83 * 4.30 g/dL respectively. The water extract of Channa striatus (30 mglkg) and the aqueous portion of chloroform:methanol extract Channa lucius (1 5 mg/kg) produced antinociceptive effect on acetic acid induced abdominal constriction test. However both extracts of three local Channa spp. failed to exhibit antinociceptive effect on hot plate test. As a reference drug, the administration of morphine (0.6 mg/kg) caused significant inhibition (p<0.05) by 99.3% in acetic acid induced abdominal constriction and 5 mg/kg of morphine produced significant increased the latency time in hot plate test when compared to control and both extracts of three local Channa spp. In conclusion, this study showed that Channa striatus extracts has more potent the anti-inflammatory and antinociceptive activities compared to the other closely related snakehead fish Channa micropelfes and Channa lucius. The extracts from Channa striafus have the potential being the antiinflammatory and antinociceptive agents.